Building a Genetics Curriculum: Needs Assessment Survey of Middle and High School Students - Jennifer C. Drew; Joy C. Jordan; Eric W. Triplett (EDIS)
MB002, a 5-page report by Jennifer C. Drew, Joy C. Jordan, and Eric W. Triplett, presents the results of a 1-page survey of 140 students at a 4-H sponsored event, which was designed to assist in developing a 4-H curriculum in genetics. Published by the UF Department of Microbiology and Cell Sciences, June 2006.